Patterns of macroinvertebrate distribution in watercourses of the Krasnoyarsk Stolby National Park (East Siberia) - Olga N. Vdovina; Elena F. Tropina; Anna Yu. Makarycheva; Marina G. Yerunova (Nature Conservation Research: Заповедная наука)
For a successful planning of the environmental monitoring, the understanding of the formation patterns of communities and their interactions with the environment is of great importance. During monitoring studies, ecosystems of the protected areas can serve as reference sites for assessing the disturbance degree, especially when anthropogenic impacts are absent or insignificant. The first and most comprehensive investigations of the fauna of benthic invertebrates in the watercourses of the Krasnoyarsk Stolby National Park were conducted in the late 1950s – early 1960s. They included a study of the faunistic composition of benthic invertebrates and zoobenthos distribution in biotopes and water bodies. In 2020–2023, the reconnaissance studies of macrozoobenthos was carried out in 24 watercourses in the Krasnoyarsk Stolby National Park, Siberia. All watercourses belong to three receiving basins of the River Bazaikha, River Yenisei, and River Mana. A total of 57 quantitative and nine qualitative samples of zoobenthos were collected. Using the non-metric multidimensional scaling (NMDS) analysis, we established the relationship between the taxonomic composition of macroinvertebrates and river basins, flow velocity, average riverbed gradient, main channel length and bottom sediment. Redundancy Analysis (RDA) was used to analyse the influence of environmental factors. The impact of nine hydrophysical and hydrochemical environmental factors on macroinvertebrates was studied. Our research made it possible to identify 104 species from eight classes of invertebrates of the zoobenthos in the surveyed watercourses. The highest species diversity was noted for Diptera. A relatively high number of Trichoptera, Ephemeroptera and Plecoptera species was also recorded. Lithorheophilic organisms, typical of streams with rocky substrates, low water temperatures and favourable oxygen conditions, dominated in the invertebrate fauna. The examined rivers had similar species composition of zoobenthos. For most streams, the similarity level made up to 60–79%. Among the studied watercourses, the highest species richness and abundance of macroinvertebrates was common for the large-in-length rivers. It was shown that flow velocity, average riverbed gradient and main channel length were most closely related and significant (p ˂ 0.05) to macroinvertebrate distribution. For streams with high and low flow rates, typical inhabitants of the rithral zone, namely larvae of Ephemeroptera and Plecoptera, as well as Gammaridae, were the differentiating forms. In two other groups, in addition to Ephemeroptera and Gammaridae, larvae of the family Chironomidae also made a remarkable contribution to differences in the species composition of streams with a greater length and a small riverbed gradient. Water temperature had the greatest effect on the total number of macroinvertebrates, while the length of the main channel, mineralisation and pH influenced it moderately.